A New Inscription of Herakas, Son of Pontikos, ᾿Αρχερμηνεὺς ᾿Αλανῶν - Pavlichenko, Natalia; Fedoseev †, Nikolaj (Hyperboreus, 2019)
In 2017, during the investigation of the necropolis of Kyz-Aul (situated in the south-eastern part of the Kerch Peninsula near the village of Yakovenkovo), a fragment of a marble plate was found. Together with pottery of the 1st–3rd, 6th–7th and 8th–10th centuries AD, it was retrieved from the ﬁll of the tomb dating to the ﬁrst centuries AD, which was robbed already in antiquity and later served as a dwelling (6th–7th centuries) and as a shed for sheep and goats (ca. 750–950 AD). On one of its sides, a Greek inscription is carved; on the other, part of a relief is discernible, viz. the head and neck of a horse to the right. The upper part, the left and, partially, the right sides of the plate are broken oﬀ, but the date according to the Pontic era (the year 501, 25th day of the month of Daeisios, i. e. 204 AD) and the preserved text allow us to reconstruct fairly reliably the name and the title of Herakas, son of Pontikos, the chief interpreter of the Alans. In addition, in this inscription a title ἄρχων αὐ[λῆς] with the same meaning as ὁ ἐπὶ τῆς αὐλῆς (“superintendent of the royal court”) is reconstructed. Herakas, son of Pontikos, is already known to us from the inscription CIRB 1053. This building inscription was found in Taman on the site of the fortress of Phanagoria already in 1910. Taking into consideration that both in CIRB 1053 and the new inscription Herakas, son of Pontikos, supervised construction works and was managing the royal court, his functions undoubtedly exceeded the functions of an ordinary interpreter from Alanian to Greek. Probably he was a mediator and a representative of the royal administration who was obliged to communicate with Alans, which played an important role in the barbarian environment of the Bosporan Kingdom during the reign of Sauromates II.